Experimental Application of Tissue Adhesives in Corneal Traumas. Issue 5 (September 2013) - Papadopoulou, Domniki N.; Sionga, Antonia; Karayannopoulou, Georgia; Natsis, Konstantinos; Komnenou, Anastasia; Mangioris, Georgios; Kalpatsanidis, Antonios; Manthos, Anastasios; Georgiadis, Nikolaos; Karampatakis, Vasileios
Purpose: To evaluate intraoperative difficulties of the use of glues for corneal trauma . Methods: Partial or full-thickness perpendicular corneal incisions (3–4 mm straight cuts) near the limbus (perpendicular or parallel to it) were made in 8 albino rabbits and were then sealed with fibrin or cyanoacrylate glue. Follow-up examinations were performed under the surgical microscope. Tissue specimens were also taken for light microscopic evaluation . Results: The cyanoacrylate glue polymerized almost immediately after application on the tissue, limiting the ability of the surgeon to oppose the corneal incisions appropriately. The fibrin glue polymerized more gradually, giving enough time for manipulations to reconstruct the wound properly and for removal of excessive glue, especially when the 2 components were applied separately. Excessive glue and crust formation on the eye surface induced irritation . Conclusions: Fibrin glue for the reconstruction of corneal wounds was easier to use than cyanoacrylate glue and caused less glue crust formation on the corneal surface. The speed of polymerization is an important factor. Excessive glue on the cornea was irritating .